An Approach to Quantify the Factors That Affect Performance Measurement System Implementation. Issue 2 (3rd April 2017) - Keathley-Herring, Heather
Abstract: Although there have been many important academic advancements in the area of performance measurement systems, many practitioners and researchers still report encountering significant challenges during practical applications. This has led to the development of research to identify factors that affect the success of performance measurement systems. Previous studies attempt to identify and evaluate these factors, but there is little evidence of the inter-relationships and overall effects of various factors on the successful implementation of performance measurement systems. This article describes an exploratory study that applies an existing approach, originally proposed to design performance measurement systems, to investigate the effectiveness of the approach in quantifying the systemic effects of success factors on the implementation of a performance measurement system. The results of this study suggest that applying this approach provides quantitative assessments of the systemic effects of the success factors, which can be used to design more robust implementation strategies.